2003
DOI: 10.1038/nature01474
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of sanctions on human altruism

Abstract: The existence of cooperation and social order among genetically unrelated individuals is a fundamental problem in the behavioural sciences. The prevailing approaches in biology and economics view cooperation exclusively as self-interested behaviour--unrelated individuals cooperate only if they face economic rewards or sanctions rendering cooperation a self-interested choice. Whether economic incentives are perceived as just or legitimate does not matter in these theories. Fairness-based altruism is, however, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
461
7
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 711 publications
(498 citation statements)
references
References 17 publications
23
461
7
7
Order By: Relevance
“…It often lowers the average income in Public Good games, despite raising the average level of contributions. In games of trust, or games involving rewards, adding the threat of punishment can decrease the menaced player's willingness to cooperate [65]. In a particularly elegant set of experiments, it has been shown that, if players of a Public Good game are offered before each round the choice between the versions with or without Punishment, many tend first to shun negative incentives.…”
Section: The Limitations Of Peer-punishmentmentioning
confidence: 99%
“…It often lowers the average income in Public Good games, despite raising the average level of contributions. In games of trust, or games involving rewards, adding the threat of punishment can decrease the menaced player's willingness to cooperate [65]. In a particularly elegant set of experiments, it has been shown that, if players of a Public Good game are offered before each round the choice between the versions with or without Punishment, many tend first to shun negative incentives.…”
Section: The Limitations Of Peer-punishmentmentioning
confidence: 99%
“…The modified versions of the Core model are applied to the analysis of human behavior in the settings of two well known lab experiments -the Trust Game of Fehr and Rockenbach [2003] and the Control Game 21 by Falk and Kosfeld [2006], which are described in detail below.…”
Section: Application To the Experimentsmentioning
confidence: 99%
“…For instance, providing additional incentives can, in contrast with standard models with selfish actors, lead to lower levels of performance and intentions seem to matter, according to Fehr and Rockenbach [2003], Falk and Kosfeld [2006] and many others 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such so-called 'peer punishment' can be effective under certain conditions (Fehr and 487 Gächter, 2000). However, it can easily be subverted by asocial punishment, not directed 488 against the defectors, but rather against the cooperators (Fehr and Rockenbach, 2003; Denant-489 Boemont et al, 2007;Herrmann et al, 2008;Nikiforakis, 2008; Nikiforakis and Engelmann, 490 2012). While the self-justice involved in peer punishment may be important for the ancestral 491 establishment of cooperation, it is not normally used in developed societies to promote 492 cooperation (Guala, 2010).…”
mentioning
confidence: 99%